2015
DOI: 10.3389/fphar.2015.00280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Fucosyl-Lactose, a Milk Oligosaccharide, on Dry Eye Model: An Example of Nutraceutical Candidate

Abstract: Purpose: Colostrum has been proposed to treat severe dryness and problematic eye lesions showing a beneficial effect. The aim of the study was to investigate the effect of 2-fucosyl-lactose, a natural sugar present in the human colostrum, in an experimental dry eye.Methods: Dry eye was induced in adult male New Zealand albino rabbits by topical administration of 1% atropine. Tear volume (Schirmer’s test), tear film breakup time (TBUT), corneal staining and tear osmolarity were assessed. Fucosyl-lactose eye dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The treatment has to be given daily, for periods of time usually higher than one year [15]. Atropine is known to interfere with lacrimation [16,17], and therefore might pose treated patients at risk of dry eye [12]. Therefore, we examined the effects on primary human corneal epithelial cells (HCE-F) of a relatively long-term treatment (96 h) with low dose atropine (1 mM, corresponding to a 0.03% solution).…”
Section: Atropine Toxicity Is Blunted By Colostrum and Fucosyl-lactosementioning
confidence: 99%
“…The treatment has to be given daily, for periods of time usually higher than one year [15]. Atropine is known to interfere with lacrimation [16,17], and therefore might pose treated patients at risk of dry eye [12]. Therefore, we examined the effects on primary human corneal epithelial cells (HCE-F) of a relatively long-term treatment (96 h) with low dose atropine (1 mM, corresponding to a 0.03% solution).…”
Section: Atropine Toxicity Is Blunted By Colostrum and Fucosyl-lactosementioning
confidence: 99%
“…25 Multiple topical administrations of 1% atropine significantly reduced the tear volume after 24 hours in an animal model. 26 Our results showed that after administration of 0.01% atropine for 6 months, there were no significant changes in the indices for aqueous production and tear stability. This might be related to the low concentration of atropine in the eye drops, and because the eye drops were only used once at night.…”
Section: Discussionmentioning
confidence: 47%
“…The significant reduction of aqueous production after AS administration is due to its antimuscarinic activity in the lacrimal gland, with evident modification of tear stability [ 26 ]. This protocol leads to the development of dry-eye syndrome in rabbits and was applied to the evaluation of the efficacy of new polymeric substances such as arabinogalactan [ 27 ], and of human natural constituents such as 2-fucosyl-lactose [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In any case, one of the main symptoms common to all types of models of dry eye is the scarce tear fluid production and all the different experimental animal models carry out measurements of aqueous tear production using Shirmer test. In the atropine-induced dry eye model in rabbits, other than a reduction of the Shirmer test score to 8.75 mm, an improvement of approximately 93.0 mOsmol/L was observed in the tear fluid of rabbits after 24 h of treatment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%